Diagnosis of Early Stage of Dirofilariasis in Carnivores - L. M. Kokolova; Л. М. Коколова (Russian Journal of Parasitology, 2019)
The purpose of the research is to study methods of dirofilariosis diagnostics in comparative aspect and give analysis of therapy and prophylactics means. Materials and methods. Blood films of spontaneously infected dogs and experiment dogs and puppies were material for research. There were 5 puppies and 12 dogs of different age. After the death from dirofilariosis in experimental dogs, organs and tissues were examined, heart was opened and sexually mature dirofilarias were found. The sample for analysis was diluted with saline, the precipitate was examined under a microscope. A thick blood smear was stained using the Romanovsky-Giemsa method and was microscopically enlarged 140 times. To study blood and detect microfilaria in the blood, concentration methods were used: the Knott method using 1ml of fresh blood and 10 ml of a 2% formalin solution, the method using a 5% solution of acetic acid. Results and discussion. All studied methods are effective for detection microfilariae in the blood samples, however, the preferred method for us was the centrifugation method with distilled water, developed by V.B. and the method of thick crushed blood drop, since the detected microfilaria larvae remained viable and were used in experiments on the viability of microfilariae. Of the 45 samples examined, 10 detected microfilariae D. immitis. However, in most cases, the final diagnosis of dirofilariasis was made after the death of the host. In the zone endemic to the dirofilariasis, it is necessary to carry out continuous treatment of water reservoirs. Residential and non-residential premises treated with insecticides. Survey and de-worming of the invasive domestic dogs are carried out in the spring-summer period. Selamectin, moxidexin, ivermectin, dectomax, novomek, otodectin and others are applied. To prevent mosquitoes from contacting pets and humans long-acting repellents in the form of a spray, powder, emulsion, lotions are the most convenient to use. Цель исследования: изучить методы диагностики дирофиляриоза в ...